2021
DOI: 10.1007/s10008-021-05017-6
|View full text |Cite
|
Sign up to set email alerts
|

A simplified methodology: pH sensing using an in situ fabricated Ir electrode under neutral conditions

Abstract: Herein, a simplified fabrication method for the producing of a pH-sensitive iridium electrode is developed. The in situ electrochemical fabrication of an iridium oxide film is optimized and shown to be achievable under neutral conditions rather than the acidic conditions hitherto employed. The formation of a pH sensitive Ir(III/IV) hydrous film is confirmed via XPS. The amperometric pH-sensing properties of this electrochemically generated material were investigated using square wave voltammetry. In the pH ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 104 publications
1
14
0
Order By: Relevance
“…Sample pH can be accurately measured in small volumes by integrating metal oxide electrodes in microfluidic channels. For example, Steinsberger et al demonstrated a RuO 2 electrode for pH measurements, while Chen et al reported an IrO x electrode . However, while we have used a similar approach in the past with ion selective electrodes, adopting this approach herein would necessitate the use of custom microfluidic cells and would make the instrument setup more complex.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sample pH can be accurately measured in small volumes by integrating metal oxide electrodes in microfluidic channels. For example, Steinsberger et al demonstrated a RuO 2 electrode for pH measurements, while Chen et al reported an IrO x electrode . However, while we have used a similar approach in the past with ion selective electrodes, adopting this approach herein would necessitate the use of custom microfluidic cells and would make the instrument setup more complex.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Steinsberger et al demonstrated a RuO 2 electrode for pH measurements, 23 while Chen et al reported an IrO x electrode. 24 However, while we have used a similar approach in the past with ion selective electrodes, 27 adopting this approach herein would necessitate the use of custom microfluidic cells and would make the instrument setup more complex. The titration process end point determination can be also done spectrometrically using a combination of an LED and a photodiode.…”
Section: System Design and Operationmentioning
confidence: 99%
See 2 more Smart Citations
“…Several traditional methods have been employed to monitor cell culture, such as the optical microscope, spectrophotometer, chromatograph, electrical sensor, and a mass spectrometer. Recent advancements in analytical methods have supplemented traditional monitoring techniques, relying on an understanding and application of microfabrication, [17][18][19] optical [12,20] and conductive [21,22] materials, sensitive signaling probes, [5] and microfluidic chip packaging. [23,24] This review summarizes the parameters used for monitoring cell culture into four main categories: cellular physiology, cellular environment, cellular metabolite, and contaminant monitoring (Figure 1).…”
Section: Introductionmentioning
confidence: 99%